Minimizing an indefinite quadratic function subject to a single indefinite quadratic constraint. (2nd January 2018) - Fallahi, S.; Salahi, M.; Terlaky, T.
Abstract: In this paper, we consider the problem of minimizing an indefinite quadratic function subject to a single indefinite quadratic constraint. A key difficulty with this problem is its nonconvexity. Using Lagrange duality, we show that under a mild assumption, this problem can be solved by solving a linearly constrained convex univariate minimization problem. Finally, the superior efficiency of the new approach compared to the known semidefinite relaxation and a known approach from the literature is demonstrated by solving several randomly generated test problems.